G14 A consensus survey on risk-based selection criteria for the next SIOP trial of 'sight-saving therapy' for children with NF1-associated optic pathway glioma (NF1-OPG). (27th April 2016) - Walker, DA; Liu, JF; Deasy, R
Abstract : Aims: The natural history of children with NF1-OPG is unpredictable, indications for therapy to save vision, using patient, imaging and visual factors have not been studied in Europe. In the previous SIOP-E NF1-OPG multi-disciplinary workshop, consensus on imaging and visual classification was achieved, including a schematic for recording patient, visual and imaging details. This survey was setup to collect opinions on selecting NF1-associated OPG patients for observation, treatment and randomisation, and assess the feasibility of a randomised trial from an external multidisciplinary group. Methods: Eight SIOP-LGG2004 centres contributed 83 NF1-OPG cases with complete imaging, visual and clinical datasets. From these, 10 cases were selected to display a range of ages on presentation and tumour locations in accordance with the PLAN classification (Figure 1 ). 1 The survey targets all medical professionals involved in the multi-disciplinary team making management decisions for NF1-OPG patients. The questionnaire consists of 32 questions to collect data on (1) management decision of 10 representative cases and reasoning, (2) information about the participant and (3) feedback on the questionnaire. This questionnaire was pre-tested among SIOP-E NF1-OPG workshop participants in late 2014 then revised in 2015. Results: Sixty-two medical professionals took part in the survey and allocated 4 cases for treatment and 2 cases for observation with consensus (>70% agreement). Respondents did not reach consensus on the management decision of 4 patients (Table 1 ); 20–43% of the respondents voted for randomisation for the four patients. Conclusions: The SIOP-E NF1-OPG group will invite more medical professionals to express their opinion on using patient, imaging and visual factors to select patients for sight-saving therapy. The results will assist the group in planning the next SIOP-LGG trial. Subgroups that did not reach consensus on treatment decision may be eligible for randomisation. Reference: Taylor T, Jaspan T, Milano G, et al . Radiological classification of optic pathway gliomas: experience of a modified functional classification system. The British Journal of Radiology 2008;81 (970):761–6